THE CALC-ALKALINE MONTE CAPO STELLA DYKES IN THE OPHIOLITIC UNIT OF THE ELBA ISLAND (ITALY): GEOLOGICAL SETTING AND COMPOSITIONAL CHARACTERIZATION - Pandeli, Enrico; Santo, Alba P.; Candido, Monica R.; Petrone, Chiara M.; Giusti, Riccardo (Ofioliti, 2014)
In this paper we studied in detail magmatic dykes filling fractures in the pillow lavas of the Ophiolitic Unit cropping out in the Monte Capo Stella Promontory (southern part of the Elba Island in the Northern Tyrrhenian Sea). The Elba Island is well known for its Tertiary complex tectonic stack of nappes, Late Miocene intrusion of acidic magmatic bodies and Fe-mineralizations. The phaneritic sub-volcanic rock (Monte Capo Stella dykes, MCSD) shows a porphyritic texture with variable pheno- and xenocrysts content. The main phenocrysts consist of plagioclase, quartz, K-feldspar and biotite. The MSCD, displaying calc-alkaline affinity, have a High-Potassium dacitic composition. Moderate fractionation and negative Eu anomaly characterize the chondrite normalised REE patterns. The mantle-normalized trace element patterns exhibit relatively high content of the most incompatible elements with negative spikes of Ba, Ta, Nb, Sr, P, and Ti. The measured 87Sr/86Sr and 143Nd/144Nd isotopic ratios are 0.708129 and 0.512209 respectively. In spite of the lack of radiometric data, the MCSD can be related to the acidic to intermediate magmatism that occurred in the interland of the Northern Apennines Chain during late Miocene-Quaternary times. In particular, the MSCD belong to the intermediate rocks of the Tuscan Magmatic Province and display petrological and geochemical characteristics closely resembling those of a mafic enclave collected in the 6.8 Ma Orano Porphyry (Elba Island) and of some 9-4 Ma High Potassium Calc-Alkaline (HKCA) Capraia Island rocks. Thus, in the context of the Elba Island, the studied dykes represent the magmatic bodies showing the most peculiar HKCA features. The intrusion age of the MCSD can be put in the time interval between the intrusion of the Orano Porphyry in Western Elba (6.8 Ma) and that of the Monte Castello dyke (5.8 Ma) in Eastern Elba, and possibly before the Central Elba Fault (CEF) activity. This study also refines the deformation history of the Ophiolitic Unit in the Elba Island defining three final brittle deformation stages.